The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1109/access.2020.2970461
|View full text |Cite
|
Sign up to set email alerts
|

A Light-Weighted CNN Model for Wafer Structural Defect Detection

Abstract: Silicon wafer is the raw material of semiconductor chip. It is important and challenging to research a fast and accurate method of identifying and classifying wafer structural defects. To this end, we present a novel detection method in terms of the convolution neural networks (CNN), which achieve more than 99% detection accuracy. Due to the wafer images are not available by open datasets, a set of imaging acquisition system is designed to capture wafer images. Digital image preprocessing technology is utilize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(24 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…In another study, Xiaoyan et al [ 20 ] developed a lightweight CNN model dubbed ‘WDD-Net’ for silicon wafer structural defect detection with a very high detection accuracy (99%). The research evaluated the WDD-Net model against two other established CNN models, one based on VGG-16 and the other based on MobileNet-v2, in which the experimental results showed that WDD-Net was five times faster than the 307 KB models, hence the term ‘lightweight’.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, Xiaoyan et al [ 20 ] developed a lightweight CNN model dubbed ‘WDD-Net’ for silicon wafer structural defect detection with a very high detection accuracy (99%). The research evaluated the WDD-Net model against two other established CNN models, one based on VGG-16 and the other based on MobileNet-v2, in which the experimental results showed that WDD-Net was five times faster than the 307 KB models, hence the term ‘lightweight’.…”
Section: Introductionmentioning
confidence: 99%
“…In several works, the defect classification from wafer and mask data with deep learning methods has been demonstrated. [7][8][9][10][11][12][13] Such methods also have been used to perform pattern matching, contour extraction, and 3D profile reconstruction from SEM images. [14][15][16] A general property of SEM images, the noise, has been addressed in further works, with goal of reducing the noise to obtain higher accuracy in the image analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Since the collection of defect images is time-consuming, recent research on generating pseudo defective images with GAN has attracted attention. Chen et al [12] uses affine transformation and naïve generative adversarial networks (GAN) to tackle the problem of having unbalanced quantities of defect-free and defective images. They expanded the number of defective images that enhanced the classifier's generalization ability.…”
Section: Introductionmentioning
confidence: 99%